Bayer-filtered image compression based on CCSDS-123 standard: A tailored approach for CubeSats - El habib BENSIKADDOUR; Youcef BENTOUTOU (Results in Optics, 2024)
CubeSats, popular for enabling affordable-access to various space missions, face challenges related to their limited resources. Image compression combined with Bayer filtering, could be a potential key to maximize the efficiency of CubeSats’ limited resources. This paper aims to customize the CCSDS-123 recommendation for lossless compression of Bayer-filtered images onboard CubeSats, with emphasis on simplicity and efficiency. The results obtained with images obtained from the Alsat-1 N CubeSat demonstrate the feasibility and satisfactory performance of the proposed approach.